(untitled) (Conferencea, 2023)
In the current conditions of increasing the independence of economic entities in the regional districts, the problem of assessing the financial potential is becoming more and more urgent. The problem of financial stability of business entities does not lose its relevance throughout the entire process of development of socio-political and economic relations of any country. This is especially true for countries undergoing global transformation processes.